Igualdade, diferença e desigualdade: gênero, raça-etnia e religião em sala de aula nos anos iniciais do Ensino Fundamental - Crociari, Simone Ribeiro Tempesta (2017)
The present work aims to analyze how female teachers from the first years of elementary school approach on gender, race-ethnicity and religion in the classroom, with a view to discussing the concepts of equality, difference and inequality. It is conceived that the universes of culture and education are connected, being it necessary that the school and its professionals are sensitive to cultures (in plural) present in this space, observing the building of bridges, the stimulus to equal dialogue and the view that the cultural differences are part of democracy, and not a problem to be overcome in the search of homogeneity. For this purpose, the question posed is: “How do teachers from the first years of elementary school approach cultural differences of gender, race-ethnicity and religion in the classroom?” The qualitative methodological approach was used, and semi-structured interviews were performed, as a means of collecting data. Additionally, interculturality was chosen as the theoretical perspective. In this study, ten elementary school teachers from a municipal school in the state of São Paulo were selected. From the analysis of data, it was possible to observe that discriminations in the school space are hardly noticed by the interviewees, and, even when they are, those teachers tend to omit themselves and/or to offer the equality discourse as a democratic principle. From this perspective, it is understood that it is common for the children to be deemed innocent and devoid of prejudice, which makes it unnecessary to promote debates on diversity issues. Such analyses show the necessity that initial and continuing education address cultural diversity issues, in order to raise awareness in those professionals, which often includes admitting one’s own prejudice in order to learn how to handle it. The present work intends to defend that this will be a possible way to face the undeniable conflicts in school, with a view to supporting the constitution of a fairer, more democratic society.